Dancing fear & desire : race, sexuality, and imperial politics in Middle Eastern dance - Karayanni, Stavros Stavrou, 1965- (Cultural studies series (Waterloo, Ont.), 2004)
"Stavros Stavrou Karayanni, through historical investigation, theoretical analysis, and personal reflection, explores how Middle Eastern dance actively engages race, sex, and national identity. Close readings of colonial travel narratives, an examination of Oscar Wilde's Salome, and analyses of treatises about Greek dance, reveal the intricate ways in which this controversial dance has been shaped by Eurocentric models that define and control identity performance."--Jacket